Kebijakan Kelembagaan Kehumasan Dan Jurnalistik Untuk Meningkatkan Transparansi Dan Partisipasi Masyarakat Dalam Pemerintahan - Ndraha, Ayler Beniah; Waruwu, Eliyunus; Zebua, Dermawan; Zega, Asokhiwa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This research aims to explore the role of public relations and journalism institutions in enhancing transparency and public participation in governance. Transparency and participation are key elements that promote accountability and build trust between government and society. Using a mixed-methods approach, the study involved in-depth interviews, surveys, and document analysis at several government agencies in the district, as well as using a cross-sectional survey to measure public perceptions. The results show that public relations plays an important role in providing access to accurate and trustworthy information, which in turn improves government accountability. On the other hand, journalism serves as an independent watchdog that criticizes public policies and encourages community participation through critical coverage. Collaboration between public relations and journalism strengthens the government's ability to build positive relationships with the public, which is reflected in increased public involvement in decision-making. However, the study also identified challenges in terms of budget constraints, resistance to closed organizational cultures, and underutilization of technology in public communications. These findings highlight the importance of adequate policy support and resources for public relations and journalism to maximize their contribution to more open and participatory governance. The results of this study provide strategic recommendations to improve transparency and public participation through institutional strengthening of public relations and journalism.